Indian merchants and Eurasian trade, 1600-1750 - Dale, Stephen Frederic (Cambridge studies in Islamic civilization, 1994)
In this remarkable work of comparative economic history, Stephen Dale studies the activities and economic significance of the Indian mercantile communities which traded in Iran, Central Asia and Russia in the seventeenth and eighteenth centuries.